Lactate and cardiopulmonary responses to simulated arm-pulling and leg-kicking in collegiate and recreational swimmers - Konstantaki, M.; Swaine, I. L. (International Journal of Sports Medicine, 1999)
Investigations into the changes due to training in the metabolism of the arms or the legs in swimmers of different training status are limited. The purpose of this study was to compare the lactate and cardiopulmonary responses to simulated arm-pulling and leg-kicking in collegiate and recreational swimmers. Sixteen males (9 collegiate swimmers; SW, 7 recreational swimmers; RSW, mean+/-SD; age 22+/-3 years, body mass 81+/-9 kg, stature 1.84+/-0.06 m), gave written consent and performed continuous incremental exercise tests using either simulated front-crawl arm-pulling or leg-kicking. Lactate concentration (HLa) and oxygen consumption (VO2) were determined at 20 W intervals and at exhaustion (HLa(peak); VO2(peak)). The exercise intensity at a lactate concentration of 4 mM (EI4mM) and at exhaustion (EI(peak)) for arm-pulling and leg-kicking were also established. The arm:leg ratios for EI4mM, HLa(peak) and VO2(peak) were computed. The results showed that for arm-pulling, the SW had higher EI4mM (P=0.02), EI(peak) (P=0.006), but lower HLa(peak) (P=0.03) compared to the RSW. For leg-kicking, none of the responses differed significantly. These results suggest that it is rather the metabolism and local muscle endurance of the arms that are enhanced with competitive swimming endurance.